Rowing sportswomen motor actions formation - Volodymyr Bogush; Sergiy Getmantsev; Olga Sokol; Oksana Reznichenko; Olga Kuvaldina; Yevgen Yatsunskiy (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to study the formation of motor action sportswomen different ages depending on the level of sportsmanship. Material and Methods: girls which are specialized in a boat-racing in age groups 13-14 years inspected, 15-16 years, 17-18 years, in every group was for 20-25 persons, in all 72 sportswomen. Motive actions were probed on the method of measuring of training effect developed by us an action, and also the functional state was determined by methods: measuring of sensorimotor reaction is on sound and light irritants, speed of current of air, exactness of implementation of the set muscular effort. Results: testing showed the dynamics of forming motive, namely technique of mastering of receptions and actions, reliability, presence of errors, efficiency of active voice of consciousness in correct implementation of motion in a biomechanics relation. Conclusions: application of this method in the process of sporting preparation will allow to define quality of mastering of technique of the proper motive actions, forming of abilities, subsequent learning and becoming of more difficult motive skills